Ageing and inflammation in the male reproductive tract. (8th May 2018) - Frungieri, M. B.; Calandra, R. S.; Bartke, A.; Matzkin, M. E.
Summary: Ageing is usually characterised by a mild chronic proinflammatory state. Despite the tight association between both processes, the phenomenon has recently been termed inflammageing . Inflammation in the male reproductive tract is frequently linked with bacterial or virus infections but also with a broad range of noninfectious processes. Prostatitis, epididymitis and orchitis, among others, can lead to infertility. However, in spite of the inflammation theory of disease, chronic inflammation in male urogenital system does not always cause symptoms. With advancing age, inflammatory processes are commonly observed in the male reproductive tract. Nevertheless, the incidence of inflammation in reproductive organs and ducts varies greatly among elderly men. Inflammageing is considered a predictor of pathogenesis and the development of age‐related diseases. This article briefly summarises the current state of knowledge on inflammageing in the male reproductive tract. Yet, the precise aetiology of inflammageing in the male urogenital system, and its potential contribution not only to infertility but most importantly to adverse health outcomes remains almost unknown. Thus, further investigations are required to elucidate the precise cross‐links between inflammation and male reproductive senescence, and to establish the impact of anti‐inflammatory drug treatments on elder men's general health status.